Prevalence of Indolent Prostate Cancer in Iraq, an Autopsy Study: Prevalensi kanker prostat indolent di Irak, sebuah studi otopsi - Dr. Ibrahim Mudhafar Saadoon; Dr. Yazan Amir Seulieman; Dr. Alaa Al-Deen Al-Dabbagh (Indonesian Journal on Health Science and Medicine, 2025)
General Background Prostate cancer shows wide global variation in incidence and mortality, partly due to differences in detection strategies. Specific Background Autopsy studies provide an unbiased estimation of indolent prostate cancer prevalence by avoiding screening and reporting bias. Knowledge Gap Data on incidental prostate cancer detected through autopsy remain limited in Iraq. Aims This study aimed to estimate the prevalence of incidental or indolent prostate cancer in Iraqi men using autopsy specimens. Results One hundred male autopsies aged 40 years and above were examined, revealing prostate cancer in six cases, yielding a prevalence of 6%. All detected cancers were adenocarcinoma with Gleason score 6, confined to the prostate, and showed no capsular or seminal vesicle involvement. Cancer detection increased significantly with age. Novelty This study provides rare autopsy-based evidence on indolent prostate cancer prevalence in Iraq. Implications The findings support the need for improved prostate cancer detection, reporting systems, and public awareness programs tailored to the local context. Keywords: Indolent Prostate Cancer, Autopsy Study, Prevalence, Iraq, Gleason Score Key Findings Highlights: Occult prostate cancer was detected in a small proportion of autopsy cases Cancer detection increased consistently with advancing age All identified tumors were low grade and organ confined